2024
DOI: 10.51582/interconf.19-20.01.2024.059
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin-Helmholtz effect during hydro-vacuum dispersion of metallurgical melts

David Sakhvadze,
Gigo Jandieri,
Giorgi Sakhvadze
et al.

Abstract: This short scientific communication is devoted to the identification and assessment of the significance of the Kelvin-Helmholtz effect in the process of hydro-vacuum dispersion of industrial metallic melts. It is established that this effect, formed at the interface "liquid metal" - "water" contributes to the stable production of particles with increased mechanochemical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Perspectives for development Based on the above analysis, we concluded that there is a new possibility of improving the technology of direct alloying of steel and alloys, which is associated with the prospect of using as an active reducing agent obtained specifically for this purpose hydrogenated aluminum powder AlH 3 (H 1-5%). We were the first to obtain such a powder as a by-product of hydro-vacuum dispersion of liquid aluminum No 193 superheated at 150 o C. The observed effect was achieved by operating our hydro-vacuum dispersion unit [25] in the mode of generating a high-frequency cavitation-wave field [26] and initiating sonochemical hydrogenation reactions. According to the study of [27], the general sonochemical hydrogenation reaction of metal powder particles can be written as follows:…”
Section: Current State Of the Problemmentioning
confidence: 99%
“…Perspectives for development Based on the above analysis, we concluded that there is a new possibility of improving the technology of direct alloying of steel and alloys, which is associated with the prospect of using as an active reducing agent obtained specifically for this purpose hydrogenated aluminum powder AlH 3 (H 1-5%). We were the first to obtain such a powder as a by-product of hydro-vacuum dispersion of liquid aluminum No 193 superheated at 150 o C. The observed effect was achieved by operating our hydro-vacuum dispersion unit [25] in the mode of generating a high-frequency cavitation-wave field [26] and initiating sonochemical hydrogenation reactions. According to the study of [27], the general sonochemical hydrogenation reaction of metal powder particles can be written as follows:…”
Section: Current State Of the Problemmentioning
confidence: 99%